Colon specific delivery of miR-155 inhibitor alleviates estrogen deficiency related phenotype via microbiota remodeling. (31st December 2022) - Zhao, Lianbi; Zhou, Tian; Chen, Jianmei; Cai, Wenbin; Shi, Ruijing; Duan, Yunyou; Yuan, Lijun; Xing, Changyang
Abstract: Compelling data have indicated menopause-associated increase in cardiovascular disease in women, while the underlying mechanisms remain largely unknown. It is established that changes of intestinal microbiota affect cardiovascular function in the context of metabolic syndrome. We here aimed to explore the possible link between host intestinal function, microbiota, and cardiac function in the ovariectomy (OVX) mouse model. Mice were ovariectomized to induce estrogen-related metabolic syndrome and cardiovascular defect. Microbiota was analyzed by 16s rRNA sequencing. miRNA and mRNA candidates expression were tested by qPCR. Cardiac function was examined by echocardiography. Colon specific delivery of miRNA candidates was achieved by oral gavage of Eudragit S100 functionalized microspheres. In comparison with the sham-operated group, OVX mice showed compromised cardiac function, together with activated inflammation in the visceral adipose tissue and heart. Lactobacillus abundance was significantly decreased in the gut of OVX mice. Meanwhile, miR-155 was mostly upregulated in the intestinal epithelium and thus the feces over other candidates, which in turn decreased Lactobacillus abundance in the intestine when endocytosed. Oral delivery of miR-155 antagonist restored the protective microbiota and thus protected the cardiac function in the OVX mice. This study has established a possible regulatory axis of intestinal miRNAs-microbiota-estrogen deficiency related phenotype in the OVX model. Colon specific delivery of therapeutic miRNAs would possibly restore the microbiota toward protective phenotype in the context of metabolic syndrome.